In Loco Parentis and Positive Discipline: Building Schools as Character Building Communities - Louis Jinot Belle; Danalutchmee Chemen (Indonesian Journal of Education and Social Studies, 2025)
This study aims to explore proactive discipline strategies in preventing indisciplined actions in public secondary schools. Using a qualitative approach and case study design, data were collected through focused group discussions involving students, teachers, and principals from five institutions. Key findings suggest that an effective discipline strategy consists of three key elements: parental involvement, school leadership that serves as a surrogate parent, and the application of positive discipline. Parents' emotional and communicative involvement has been shown to shape students' character and obedient behavior. The principal's participatory leadership, which is physically present in the school environment, creates a sense of security and strengthens student compliance. Meanwhile, a positive discipline approach that focuses on character development through example, dialogue, and active student involvement can increase intrinsic awareness of disciplinary values. This research makes a conceptual contribution to the development of a collaborative, humanistic, and contextual disciplinary management framework. The practical implications of this study include the need for systemic integration of all three strategies in national education policy to create a sustainable culture of discipline in secondary schools.